COVID-19 vaccine-readiness for anti-CD20-depleting therapy in autoimmune diseases. (1st August 2020) - Baker, D; Roberts, C A K; Pryce, G; Kang, A S; Marta, M; Reyes, S; Schmierer, K; Giovannoni, G; Amor, S
Summary: Although most autoimmune diseases are considered to be CD4 T cell- or antibody-mediated, many respond to CD20-depleting antibodies that have limited influence on CD4 and plasma cells. This includes rituximab, oblinutuzumab and ofatumumab that are used in cancer, rheumatoid arthritis and off-label in a large number of other autoimmunities and ocrelizumab in multiple sclerosis. Recently, the COVID-19 pandemic created concerns about immunosuppression in autoimmunity, leading to cessation or a delay in immunotherapy treatments. However, based on the known and emerging biology of autoimmunity and COVID-19, it was hypothesised that while B cell depletion should not necessarily expose people to severe SARS-CoV-2-related issues, it may inhibit protective immunity following infection and vaccination. As such, drug-induced B cell subset inhibition, that controls at least some autoimmunities, would not influence innate and CD8 T cell responses, which are central to SARS-CoV-2 elimination, nor the hypercoagulation and innate inflammation causing severe morbidity. This is supported clinically, as the majority of SARS-CoV-2-infected, CD20-depleted people with autoimmunity have recovered. However, protective neutralizing antibody and vaccination responses are predicted to be blunted until naive B cells repopulate, based on B cell repopulation kinetics and vaccination responses, from published rituximab and unpublished ocrelizumab (NCT00676715, NCT02545868) trial data, shown here. This suggests that it may be possible to undertake dose interruption to maintain inflammatory disease control, while allowing effective vaccination against SARS-CoV-29, if and when an effective vaccine is available. Graphical Abstract: